Specific gut microbiome and metabolome changes in patients with continuous ambulatory peritoneal dialysis and comparison between patients with different dialysis vintages - Li, Jiaqi; Xing, Haitao; Lin, Wei; Yu, Hangxing; Yang, Bo; Jiang, Chen; Zhang, Jin; Wu, Ruoxi; Ding, Fengmei; Pei, Ming; Yang, Hongtao (Frontiers in Medicine, 2024)
Background:Previous studies have found that PD patients have intestinal flora disturbances, so we speculate that intestinal flora and its metabolites may be the regulatory factors in long-term therapy of PD. Methods: It is a cross-sectional study based on clinical data and biological samples of 72 patients. The intestinal microecological characteristics of CAPD patients were comprehensively evaluated by combining the intestinal microflora structure, enterotoxin and receptor (serum LPS and LBP), intestinal barrier function index (serum D-Lactate), intestinal uremic toxin (serum IS, PCS, TMAO), fecal SCFAs and other multi-dimensional and multi-omics studies.Furthermore, the changes of intestinal microecology in CAPD patients of different dialysis vintages were further explored, and the correlations between intestinal microecology indicators and some clinical indicators were analyzed. Fecal and serum samples were collected from PD patients, ESRD patients and healthy volunteers . Fecal samples were subjected to microbiome (16S rDNA) and SCFA (GC‒MS) analyses. Serum samples were subjected to LPS, LBP, D-lactate, IS, PCS, and TMAO (ELISA) analyses. Results: The diversity and richness of intestinal flora in CAPD patients were lower than those in healthy people and ESRD patients, and the microflora structure was different. The abundance of Bacteroidaceae, Bacteroides, Faecalibacterium of CAPD patients decreased. Proteobacteria, Enterobacteriaceae and Escherichia-Shigella increased their colonization (LDA>4). In CAPD patients of different dialysis vintages, there was no significant change in the diversity and richness of microflora, and the microflora structure of PDC group was significantly different from that of PDD, which the abnormal expansion of enterobacter group was more prominent in PDC and the abundance of Bacteroides group was relatively higher in PDD. Intestinal barrier damage, intestinal uremic toxin accumulation and short-chain fatty acid reduction were observed in CAPD patients.The intestinal microecological disorder of PDC group, while that of PDD group showed a better trend. Conclusions: It is initially considered that the mechanism of intestinal microecology is a potential target for intervention in the diagnosis and treatment of CAPD and incorporating intestinal microecosystem monitoring into the long-term management of CAPD patients is a new strategy.